Determinants for Predicting Polyorganic Functional Changes of the Musculoskeletal System in Children with Various Degrees of Joints Hypermobility - Liasota, Tetiana; Tonkopei, Yuliia; Юрій, Курнишев; Olha skyba; Viktor Bondarenko; Tetiana Buhaienko (Аcta Balneologica, 2023)
Aim: The aim of the work was to study the presence of determinants for predicting the local structures involvement of the musculoskeletal system against the background of joint hypermobility in children. Materials and Methods: The study involved 446 children aged from four to six years. The study plan includes: copying the data of a comprehensive medical examination; determination of joint hypermobility by goniometry and evaluation according to the criteria of presence and degree of joint hypermobility by the method of C. Carter, J. Wilkinson--in the modification of P. Beighton; application of clinical and physiological methods (functional testing, genealogical analysis) and methods of mathematical data processing. Results: The significance hierarchy of morpho-functional features in relation to the further development of the pathological process in children with one of the main manifestations of undifferentiated …